Pengaruh Npf, Fdr, Dan Dewan Pengawas Syariah Terhadap Profitabilitas Bank Umum Syariah - Zahra, Najwa Naa'imatu; Munawaroh, Azizatul (JURNAL MUHAMMADIYAH MANAJEMEN BISNIS, 2026)
This study aims to analyze the effect of Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Sharia Supervisory Board (DPS) on the profitability of Islamic Commercial Banks in Indonesia for the period 2021–2024. The study uses a quantitative approach with panel data obtained from the annual financial reports of Islamic commercial banks. The analysis method used is panel data regression with a Random Effect Model (REM) processed using EViews 13.The partial test results show that NPF has a positive and significant effect on profitability, while FDR and DPS have a negative but insignificant effect on profitability. Simultaneously, NPF, FDR, and DPS have a significant effect on profitability. The coefficient of determination (R²) value of 0.202 indicates that 20% of the variation in profitability can be explained by NPF, FDR, and DPS, while the remaining 80% is influenced by other variables outside the research model. These findings indicate that financing quality plays an important role in determining the profitability of Islamic commercial banks, while liquidity and Islamic supervisory structure factors do not yet contribute significantly individually.